An empirical study of oil and gas value chain agility in the UAE. Issue 9 (29th November 2018) - Shqairat, Ala; Sundarakani, Balan
Abstract : Purpose: The purpose of this paper is to investigate the agility of oil and gas value chains in the United Arab Emirates (UAE) and to understand the impact of implementing supply disruption (SD) strategies, outsourcing strategies (OS) and management strategies (MS) on oil and gas value chain agility (VCA). The results can support the oil and gas industry across the UAE to build resilience in the value chain. Design/methodology/approach: The research design consists of a comprehensive literature review, followed by questionnaire-based survey responses of 106 participants and comprehensive statistical analysis, thus validate the developed theoretical framework and contribute to both practical and methodological approaches. Findings: The findings indicate that oil and gas value chain in the UAE has moderate a significant degree of SD, when OS in place that are synchronized with the overall MS. Among the hypotheses developed, two were accepted thus warranting both SD strategies ( r =+0.432) and MS ( r = +0.457) found to have a positive moderate effect on VCA. The third hypothesis was rejected by revealing OS ( r =+0.387) found to have a positive moderate relationship with VCA. Therefore, implementation of all three strategies has a positive moderate effect on the agility of the value chain and, therefore, supports to sustain competitive position. Research limitations/implications: Some of the limitations of this research include the geographic coverage of the study region and other methodological limitation. Practical implications: The research provides guidance for oil and gas supply chain managers to better understand the critical factors that impact and determine VCA. The paper also describes relevant strategies that should be taken into consideration by these managers in order to build their agile value chains. Social implications: The research contributes to the social dimensions of supply chain sustainability of how resilient is the oil and gas value chain during uncertain conditions, so that it can respond to uncertain changes in order to contribute to corporate social responsibility. Originality/value: This research is the first of its kind in the UAE region to assess the link between dimensions of agile value chain, OS, SD strategies and MS primarily from the Emirates of Abu Dhabi and Dubai.